The Poor and the Poorest, Fifty Years On - Ian Gazeley; Andrew T. Newell; Kevin Reynolds; Rebecca Searle (Institute for the Study of Labor (IZA), 2014)
We re-explore Able-Smith and Townsend's landmark study of poverty in early post WW2 Britain. They found a large increase in poverty between 1953-4 and 1960, a period of relatively strong economic growth. Our re-examination is a first exploitation of the newly-digitised Board of Trade Household Expenditure Survey data set for 1953/4. Able-Smith and Townsend used only a small part of this data source. We find that Able-Smith and Townsend substantially over-estimated the rise in absolute poverty and also substantially under-estimated the rise in relative poverty. Their and our findings on poverty reflect a large rise inequality in the distribution of expenditure among British households. This rise is related to a rise in the preponderance of pensioner households, who, for instance, account for all the poor households in the 1961 Family Expenditure survey.
Keywords: N34; I32; J12; 330; poverty; inequality 1950s; Britain